Analisis Pelayanan Prima Terhadap Loyalitas Pelanggan Pada Hotel Megaria - Semuel Batlajery (Musamus University, Merauke Papua Indonesia., 2019)
The purpose of this research is to know the Service Excellence analysis of customer loyalty at Hotel Megaria Merauke. Methods: Quantitative approaches, data sources: primary data and secondary data, data collection techniques: observations, interviews and questionnaires. Population and samples: numbering 40 respondents using total sampling and data analysis techniques: simple linear regression assisted by SPSS. The results of this study showed a regression coefficient of X of 0.254 meaning that excellent service variables have a positive and significant influence on customer loyalty which means that the service affects customer loyalty in Hotel Megaria Merauke.